Dialectical Communication of Islamic Sharia in Dayah Culture of Banda Aceh - Choiriyati, Wahyuni; Rahmat Hidayat, Dadang; Karlinah, Siti; Saeful Muhtadi, Asep (International Journal of Engineering and Technology, 2018)
Dayah has a role in the religious tradition of the Acehnese in making ulema group into an instrument linked in the discussion of Islamic Sharia. People relate the ups and downs of the implementation of Islamic Sharia in Aceh to the role of ulema. Studies of dayah culture in Aceh questioning the role of ulema in the implementation of Islamic Sharia and how dialectical communication from the ulema succeeds the implementation of Sharia Qanun in Aceh. The progress of dayah depends on the leading ulema instead of the name of dayah. Through a case study, this study analyzes the cultural communication created in dayah by studying the character of communication between ulema and dayah students. The concept of habitus as a foundation of the theory applied to see dayah as an arena for communication between ulema and dayah students in legitimizing the value of Sharia becomes a practical and natural action. As a result of habitus, Dayah grows naturally into a structured habit through a long, internalized and acculturated social process in the community. Data are obtained through in-depth interviews with the Acehnese figures and people during the period of 2017. Triangulation is applied to test the validity of data.Â Â